Sustainable development goals (SDGs) for education in Nigeria: an examination of Etisalat corporate social responsibility in Nigeria's post-basic education sector. Issue 5 (1st November 2020) - Bello, Ismail
ABSTRACT: The post-basic education sector is critical to the achievement of the SDGs because this sector increase employability, helps build life skills, and most importantly, improves youth development. No doubt, if post-basic education improves, it will help in the actualisation of the seventeen goals of SDG. Findings reveal that Etisalat intervention in post-basic education includes Adopt a school programme, STEM camps for girls to promote knowledge of science education, career-counselling session serves as an opportunity for students to learn about career opportunities that they could select as they proceed to tertiary institutions. The adoption of has led to improvements in infrastructure and learning outputs at the post-basic-sector. All these are done in accordance with the SDGs. This study adds to the literature on the role of non-state actors especially Multinational Corporations towards developing the education sector in Nigeria and the achievement of sustainable development goals around the globe.